Going beyond the technology: Considerations in translating electronic case report forms - Amy E. Krefman; Luke V. Rasmussen; Crystal Santillanes; Mary Beth Tull; Patricia Bustamante; Alan Kuang; Hongyan Ning; Yaojie Wang; Barbara M. Gonzalez; Eugenia I. Manrique; Lauren B. Bonner; Jody D. Ciolino (Journal of Clinical and Translational Science, 2025)
Through a series of example research studies, we illustrate processes in translating case report forms to increase language diversity in study populations while simultaneously highlighting implications for data collection and analyses. The Northwestern University Data Analysis and Coordinating Center manages the translation of participant-facing study documents into languages other than English through a process that has been refined over several years, adjusting for changes in technical capabilities in electronic case report forms. This approach to manage, examine for context, and implement certified case report form translations offers an efficient workflow to streamline data capture in multiple languages.